Teachers’ Methodologies and Sources of Information on HIV/AIDS for Students with Visual Impairments in Selected Residential and Integrated Schools in Ghana - Hayford, Samuel K.; Ocansey, Frederick (Journal of the American Academy of Special Education Professionals, 2017)
This study reports part of a national survey on sources of information, education and communication materials on HIV/AIDS available to students with visual impairments in residential, segregated, and integrated schools in Ghana. A multi-staged stratified random sampling procedure and a purposive and simple random sampling approach, where appropriate, were used to select 83 students with visual impairments to participate in a survey. Descriptive and inferential statistics, including frequency distribution, percentages, and chi-square (X[superscript 2]) test, were used to analyze the data. The findings revealed that teachers used a variety of sources of information such as newspapers, storybooks, prescribed textbooks and recorded materials, and workplace HIV/AIDS policies to teach HIV/AIDS lessons to students with visual impairments. Additionally, teachers relied more on discussion, storytelling and lecture method, rather than interactive methodologies to teach HIV/AIDS lessons. Chi-square (X[superscript 2]) computation at 0.05 significant level revealed that none of the students’ responses was independent on gender. Recommendations were offered to the Ghana’s Ministry of Education for consideration.